(untitled) (American Journal of Islam and Society, 2015)
This paper aims to engage in a critical comparison of the spiritual authority of the awliyā’ in the Shi‘i and Sufi traditions in order to examine an area of Islamic belief that remains unclearly defined. Similarities between Shi‘i and Sufi doctrine have long been noted, but little research has been conducted on how and why they developed. Taking a central tenet of both, walāyah, the paper discusses several of its key aspects as they appear recorded in Shi‘i ḥadīth collections and as they appear later in one of the earliest Sunni Sufi treatises. By extention, it seeks to explore the identity of the awliyā’ and their role in relation to the Twelve Imams. It also traces the reabsorption into Shi‘i culture of the Sufi definition of walāyah via two examples: the works of one branch of the Dhahabi order and those of Allamah Tabataba’i, a popular twentieth-century Iranian mystic and scholar.